Validating the Usefulness of the “Random Forests” Classifier to Diagnose Early Glaucoma With Optical Coherence Tomography - Asaoka, Ryo; Hirasawa, Kazunori; Iwase, Aiko; Fujino, Yuri; Murata, Hiroshi; Shoji, Nobuyuki; Araie, Makoto (American journal of ophthalmology, 2017)
To validate the usefulness of the “Random Forests” classifier to diagnose early glaucoma with spectral-domain optical coherence tomography (SDOCT). design: Comparison of diagnostic algorithms. setting: Multiple institutional practices. study participants: Training dataset included 94 eyes of 94 open-angle glaucoma (OAG) patients and 84 eyes of 84 normal subjects and testing dataset included 114 eyes of 114 OAG patients and 82 eyes of 82 normal subjects. In both groups, OAG eyes with mean deviation (MD) values better than −5.0 dB were included. observation procedure: Using the training dataset, classifiers were built to discriminate between glaucoma and normal eyes using 84 OCT measurements using the Random Forests method, multiple logistic regression models based on backward or bidirectional stepwise model selection, a least absolute shrinkage and selection operator regression (LASSO) model, and a Ridge regression model. main outcome measures: Diagnostic accuracy. With the testing data, the area under the receiver operating characteristic curve (AROC) with the Random Forests method (93.0%) was significantly (P < .05) larger than those with other models of the stepwise model selections (71.9%), LASSO model (89.6%), and Ridge model (89.2%). It is useful to analyze multiple SDOCT parameters concurrently using the Random Forests method to diagnose glaucoma in early stages.